INCREASING ENGLISH LEARNING OUTCOMES THROUGH PROBLEM-BASED LEARNING (PBL) MODEL - Mardhiyah Pohan; Muhammad Munawir Pohan (Universitas Muhammadiyah Makassar, 2022)
This research aims to describe improving student learning outcomes in English subjects using a problem-based learning model in procedural text material. This type of research is classroom action research using Kurt Lewin's model. This research is located at MTsS PTP-VI Berangir, North Labuhanbatu Regency, North Sumatra Province. The subjects in this research were all 28 students of class IX-D. This research was carried out within one month, in August, the odd semester of the 2022-2023 school year. The data analysis technique used in this research is descriptive quantitative with the narrative test of learning outcomes with a frequency distribution table. Data collection tools in this research are observation and learning outcomes tests. This research procedure was carried out in cycles, cycles I and II, which consisted of planning, implementation, observation, and reflection. The research results show that the completeness of student learning outcomes in the first cycle is 75.00%, students who achieve completeness are 21 students, while those who have not achieved completeness are seven. Furthermore, in Cycle II, the percentage of students who complete learning outcomes increased by 92.86%. Students who achieved completeness were 26 students, while those who had not achieved completeness were two students.